Financing decisions after partial privatization in China: Can a stock market quotation really provide discipline? - Huyghebaert, Nancy; Quan, Qi; Sun, Lijian (Journal of Financial Intermediation, 2014)
This paper uses the framework developed by Helwege and Liang (1996) to investigate the post-listing financing decisions of 221 Chinese state-owned enterprises that were partially privatized via the stock market in 1994–1999. First, we estimate a logit panel data model to examine the decision to raise external funds, either bank loans or equity. Our results show that the probability of raising external finance is positively correlated with the firm’s cash shortage, but only if non-cash working capital is included in the definition of the deficit. In contrast, firms with a cash surplus are less likely to tap external financial markets. Second, we examine the type of security issued and find that default risk negatively affects the probability of completing a stock offering, while firm-level information asymmetries are not significant. Overall, we document some important differences between the firms where the government retained its majority stake and those where it relinquished it; we link these to differences in the firms’ governance and access to financial markets.